Data visualization design for the analysis of the extinction risk of species groups in the American continent - Camacho-Mata, Nicole (2023)
The data visualization of this project aims to provide an easy and intuitive way to identify relationships and conclusions between the red list index, human development index, population density and CO2 emissions; from 2005 to 2018, reported in the countries of the American continent. The methodology established in the "Dashboard design cookbook" elaborated by Ph.D. Franklin Hernández-Castro was used, which includes the research and design process through iterative stages of topic selection, data collection and the definition of the relationship between them, development of the objective questions, data cleaning, exploration and selection of the paradigm, implementation and validation of the digital product. The main findings detected in the validation phase, determine that the visualization reached an acceptable level in terms of the interpretation of the information provided and the relationship of the data, as well as the ease of interaction as an integrated system. On the other side, it is satisfactory with a score of 95, obtained in the usability test, being qualified as easy to use. Finally, it should be noted that this visualization seeks to generate analysis and conclusions in order to provide a starting point, giving way to specialized research to investigate the causes of the risk of extinction of species, and in turn create a decision making based on this issue for the benefit of the population and nature.